2013
DOI: 10.1002/cne.23423
|View full text |Cite
|
Sign up to set email alerts
|

Birthdating of myenteric neuron subtypes in the small intestine of the mouse

Abstract: There are many different types of enteric neurons. Previous studies have identified the time at which some enteric neuron subtypes are born (exit the cell cycle) in the mouse, but the birthdates of some major enteric neuron subtypes are still incompletely characterized or unknown. We combined 5-ethynynl-2’-deoxyuridine (EdU) labeling with antibody markers that identify myenteric neuron subtypes to determine when neuron subtypes are born in the mouse small intestine. We found that different neurochemical classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 72 publications
3
87
0
Order By: Relevance
“…Qualitatively, the densities of EGFP + and NOS1 + neurons (i.e., EGFP -) in the colons of NGF -/-pups were comparable to those seen in age-matched NGF +/+ and NGF +/-siblings (data not shown). No calretinin + myenteric neurons were seen in pups at this age, likely due to the fact that calretinin expression by murine myenteric neurons commences on the day of birth (Bergner et al, 2013). RT-PCR revealed comparable trkA mRNA levels in the colons of postnatal day 1-2 NGF +/+ , NGF +/-, and NGF -/-siblings (data not shown); these data show that trkA expression persists in the colon of postnatal mice in spite of a loss of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 11 NGF.…”
Section: Responses By Myenteric Neurons To a Loss Of Functional Ngfmentioning
confidence: 84%
“…Qualitatively, the densities of EGFP + and NOS1 + neurons (i.e., EGFP -) in the colons of NGF -/-pups were comparable to those seen in age-matched NGF +/+ and NGF +/-siblings (data not shown). No calretinin + myenteric neurons were seen in pups at this age, likely due to the fact that calretinin expression by murine myenteric neurons commences on the day of birth (Bergner et al, 2013). RT-PCR revealed comparable trkA mRNA levels in the colons of postnatal day 1-2 NGF +/+ , NGF +/-, and NGF -/-siblings (data not shown); these data show that trkA expression persists in the colon of postnatal mice in spite of a loss of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 11 NGF.…”
Section: Responses By Myenteric Neurons To a Loss Of Functional Ngfmentioning
confidence: 84%
“…A recent study demonstrated that the birthdate of Hu+ neurons extends from E10.5 to P0 in the mouse SI (28). Subsequent to their birthdate it is thought that neurons acquire their neurotransmitter identity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this phenotype was reproduced in mice with ENSspecific deletion of the common TLR signal transducer MyD88 (111), suggesting that TLR4 signaling is a cell-autonomous requirement within ENS lineages. Since the vast majority of nNOS + enteric neurons are born during embryogenesis (18,19), these experiments indicate that TLR4 is either required for the late expression of the molecular profile of specific subsets of enteric neurons or for their survival within the microenvironment of the postnatal gut. In support of the latter idea, Anitha and colleagues showed that LPS promoted the survival of cultured enteric neurons in an NF-κB-dependent manner (111).…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 91%
“…Nucleotide analog (such as BrdU) incorporation during embryogenesis in conjunction with marker analysis in adult mice has demonstrated that enteric neuron subtypes are generated during specific but overlapping periods of development. Thus, 5-HT + enteric neurons are among the first to be born during embryogenesis, while CGRP + neurons are generated mostly postnatally (18,19). Unlike many parts of the CNS, the period of enteric gliogenesis overlaps extensively with neurogenesis: it commences at around midgestation (when neurogenesis is at its peak) and starts to decline postnatally (17).…”
Section: Introductionmentioning
confidence: 99%